Diagn Interv Radiol 2022
DOI: 10.5152/dir.2022.2111504
|View full text |Cite
|
Sign up to set email alerts
|

Use of specific contrast-enhanced CT regions of interest to differentiate renal oncocytomas from small clear cell and chromophobe renal cell carcinomas

Abstract: PURPOSE We aimed to examine the usefulness of utilizing a specific contrast-enhanced computed tomography (CT) region of interest (ROI) to differentiate renal oncocytoma (RO) from small clear cell renal cell carcinoma (ccRCC) and chromophobe renal cell carcinoma (chRCC). METHODS A retrospective analysis of pre-contrast phase (PCP), corticomedullary phase (CMP), and nephro­graphic phase (NP) contrast-enhanced CT images of the histopathologically confirmed initial cohort (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Similarly, Zhu et al identified age, irregular tumor margin, and low tumor enhancement as independent predictors of high tumor grade [ 37 ]. We also found statistically significant lower TAV, TEV, and RER of aggressive RCC in NP and EP, which may be due to the difference of microvessel density and micronecrotic areas between aggressive and non-aggressive RCC [ 37 , 39 , 40 ]. Because of the less enhancement of renal tumor compared to the surrounding renal cortex, the NP was commonly considered as the most sensitive phase for characterizing renal masses.…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, Zhu et al identified age, irregular tumor margin, and low tumor enhancement as independent predictors of high tumor grade [ 37 ]. We also found statistically significant lower TAV, TEV, and RER of aggressive RCC in NP and EP, which may be due to the difference of microvessel density and micronecrotic areas between aggressive and non-aggressive RCC [ 37 , 39 , 40 ]. Because of the less enhancement of renal tumor compared to the surrounding renal cortex, the NP was commonly considered as the most sensitive phase for characterizing renal masses.…”
Section: Discussionmentioning
confidence: 79%